(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
The use of an effective assessment system in the educational process has always been a major issue in universities. By assessing the results of learning, universities solve the problems of providing competitive scholarships, analyze the quality of educational services, and in conclusion, measure the backup of knowledge and professional competences, acquired by students. Therefore, assessments given to learning, play an important role in evaluating the quality of education. However, currently, there is no unambiguous approach to the study of assessment systems used in universities, since the “center of gravity” of assessment is gradually shifting from the field of knowledge acquisition to the field of career abilities and skills of students. Furthermore, in the current era of digitalization, the acquisition of knowledge by a student does not encounter particularly great difficulties, since various knowledge-based information sources are becoming available and open access on the Internet Network. Besides, today the existence of a competitive market employers are considered a priority to hire university graduates, who are mostly distinguished not by the knowledge they have accumulated during university study, but by their professional skills. The purpose of the research is to propose a methodology for assessing learning at universities that would take into account not only the perception of knowledge, but first of all, the level of acquisition of professional skills by the graduate. Therefore, the use of assessment approaches based on the learning outcomes presented by professional educational programs is emphasized here. Moreover, questions arise regarding the approaches to assessing learning outcomes, since they are measured, on the one hand, by the student’s academic workload, and, on the other hand, by the knowledge accumulated during the course of study or the acquisition of professional skills. In our days, the labor market is more valuating not only the accumulated knowledge of graduate students, but more their abilities and skills in working practice. Consequently, it is coming essential to answers a question “What you can do”, but not “What you distinguish and know”. The novelty of the research is the proposal of a methodology for assessing study at universities by learning outcomes and academic credit dimensions. The presented methodology is distinguished by the fact, that the grading system takes into account not only the performance of achieving the outcomes provided by the vocational educational program, but also the degree of academic workload of the student during the study period. Moreover, this combination also implies a system of task diversification, taking into account the educational workload (credit distribution) according to the required study tasks.